Caracterización de los lazos parentales en estudiantes de pregrado de la Universidad de Antioquia (2009)
ABSTRACT: The current article presents a characterization of the Universidad de Antioquia students’ parental bonding. Such characterization was achieved through a sample of 232 persons with ages between 16 and 46 years old. It was used the test Parental Bonding Instrument (P.B.I) in his adapted version for Colombian population. The test was originally developed by Parker, Tupling & Brown in 1979, and adapted by Gómez, Vallejo, Villada & Zambrano in 2007. This account of research results is based upon the attachment theory developed by John Bowlby, and pretends to bring information that could be useful for intervention in different areas of the mental health field.